FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS - Rahmi, Rika (Politeknik Kesehatan Kemenkes Bengkulu, 2013)
The purpose of this study was to determine the factors related to the abortion. Design Cross Sectional study using primary data, the population of pregnant women ≤ 20 weeks bleed by 2011 as many as 309 respondents, the study sample was taken with accidental sampling amounted to 55 people with primigravida as exclusion criteria, using the format of data collection, analyzed by univariate, bivariate with Chi-Square test and multivariate multiple logistic regression. The results show (40%) of maternal aged <20 or > 35 years (32.7%) had parity > 3, (30.9%) no history of abortion, (40%) pregnancies distance <2 years (18,2%) no maternal disease, (76.3%) experienced abortion. The results of Chi-Square test, age obtained p = 0.006, p = 0.038 obtained parity, history of abortion obtained p = 0.012, spacing pregnancies obtained p = 0.030, maternal disease obtained p = 0.565 showed there is significant relationship between age, parity, history of abortion, the distance pregnancy by abortion, and there is no significant relationship between maternal disease and abortion. Distance pregnancy dominant factors associated with the incidence of abortion (OR: 12.364).